Sharia Economic Transaction Academic Effectiveness on the Level of Community Well-Being - Ariwibowo, Prasetio; Heryadi, Deny; Muzdalifah, Muzdalifah (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2023)
The purpose of this study is to establish the level of public understanding on the use of Sharia economic transaction contracts to improve people's welfare on a regular basis. Purposive sample of 58 respondents was utilized in this quantitative descriptive study. Multiple regression analysis is used in the study approach, with SPSS 23.00 as a data analysis test tool. In this study, observations, questionnaires, and interviews were the primary data collection methods. Secondary data is provided by the Central Bureau of Statistics and the Ministry of Religion. According to the findings of this study, many types of Islamic economic transaction contracts have had a significant impact on the degree of social welfare thus far, indicating that society is becoming increasingly massive with the principles of Murabahah, Salam, Ijarah, and Mudharabah.